New algorithm of mine slope reliability based on limiting state hyper-plane and its engineering application - Liu, Zhi-xiang; Tang, Zhi-xiang; Wang, Wei-hua; Sun, Jing-jing; Peng, Kang (Journal of Central South University, 2015)
Due to the influence of joint fissure, mining intensity, designed slope angle, underground water and rainfall, the failure process of mine slope project is extremely complicated. The current safety factor calculation method has certain limitations, and it would be difficult to obtain the reliability index when the performance function of reliability analysis is implicit or has high order terms. Therefore, with the help of the logistic equation of chaos theory, a new algorithm of mine slope reliability based on limiting state hyper-plane is proposed. It is shown that by using this new reliability algorithm the calculation of partial derivative of performance function is avoided, and it has the advantages of being simple and easy to program. The new algorithm is suitable for calculating the reliability index of complex performance function containing high order terms. Furthermore, the limiting state hyper-plane models of both simplified Bishop’s and Janbu’s method adaptive to slope project are obtained, and have achieved satisfactory effect in the study of mine slope stability in Dexing copper open pit.